Frequency domain characterisation of the sound insulation performance of wooden doors and optimal design of high performance wooden doors - Caifeng Long; Xiaochuan Song; Dapeng Xu; Xu Zhu (Scientific Reports)
Abstract As an important component of the building, the sound insulation performance (SIP) of doors greatly influences the quality of the indoor acoustic environment. Therefore, this paper presents a systematic study on the SIP of wooden doors. Firstly, this study comparatively analyzes SIP across distinct core structures in both fully assembled door systems and isolated door panels, aiming to identify frequency-dependent acoustic variations across standardized bands. Secondly, acoustic finite element modeling and Gompertz’s theory of the rectangular gap sound transmission coefficient are used to further analyze the SIP of the wooden door structure across different frequency bands. This reveals the inherent relationship between the core structure, the sealing material, and the SIP of the wooden door. The results show that the SIP of the three core structures for the entire door can range from 24 dB to 27 dB. Among them, the core structure has a greater impact on low-frequency SIP, while the sealing structure has a more notable effect on high-frequency SIP. Therefore, after optimizing the wooden door design, the sound SIP can be increased by 5 dB to 8 dB. This study establishes a theoretical framework and practical design protocols for high-performance sound-insulated wooden doors, critically enabling architectural acoustic environment optimization.